Transforming Islamic Religious Education Learning from Lecturing to Participatory Methods in Society 5.0 - Tri Sutrisno; Ridho Arka Putra Utama; Mukmin Mukmin (ISTIFHAM, 2025)
The development of education in the era of Society 5.0 demands significant changes in learning approaches, including in Islamic Religious Education (IRE), where lecture-based methods have long dominated. This study aims to analyse the transformation of Islamic Religious Education (IRE) learning methods from a lecturing approach to participatory methods by reviewing various literature and relevant research published in nationally accredited journals. This research employs a literature review and thematic analysis to identify patterns, trends, and implications arising from this shift in learning approaches. The findings indicate that the lecture method has limitations in developing 21st-century competencies such as critical thinking, creativity, collaboration, and digital literacy. Conversely, participatory methods have been proven more effective in enhancing student engagement, deepening conceptual understanding, and strengthening the internalisation of religious values through interactive and reflective activities. This transformation also requires support in the form of teachers’ pedagogical competence and digital literacy, school infrastructure readiness, and flexible curriculum policies. The study concludes that participatory methods constitute a strategic approach in IRE learning to address the challenges of the Society 5.0 era and to shape students who are religious, adaptive, and well-characterised.